Factors influencing student learning outcomes and Satisfaction: A case study approach - AL-Harsoosi, Najwa; AL-Harsoosi, Yuzah; Thottoli, Mohammed Muneerali (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
Purpose: Learning outcomes play a critical role when evaluating educational programs' success and educational institutions' responsibility to deliver high-quality instruction. Educational institutions may consider improvements to fulfill the requirements of students better and enhance their emotional elements to increase interest in learning by identifying areas of strength and weakness through student learning outcomes and satisfaction evaluations. Hence, the study examines the factors for assessing student learning outcomes and Satisfaction. Methodology: A quantitative research method was utilized in this study, and 180 sample data was collected. This study employed a quantitative research design, collecting 180 sample data from students at the College of Economics, Management, and Information Systems, University of Nizwa, Oman. SEM-PLS software has been used to analyze the collected data. Findings: According to the study, educational quality (EQ) significantly impacted students' Satisfaction (SS) but not learning outcomes. There was no discernible impact of student involvement on learning outcomes or Satisfaction. Similarly, support resource quality (SRQ) does not significantly affect student learning outcomes. However, SRQ has a substantial effect on students' Satisfaction. Thus, high-quality education indicates that enhancing the learning environment should be a top priority for educational institutions. For students, self-regulated learning and metacognition are essential. Educators should constantly update and improve the curriculum to incorporate cutting-edge teaching techniques and current pedagogical trends.